Organizational Commitment berdasarkan Three Component Model dalam Partisipasi Mahasiswa - Berliana Okta Fitriani; Adira Mutiarasari; Muhammad Nurrohman; Kitna Kinovanta; Khairish Salsabila; Joko Tri Nugraha (Fakultas Ilmu Administrasi Universitas Krisnadwipayana Jakarta, 2026)
This study aims to analyze students’ interest in participating in student organizations (Himpunan Mahasiswa/HIMA) and identify the influencing factors using the Three Component Model of organizational commitment (affective, continuance, and normative). This research employs a descriptive quantitative approach with a sample of 90 students from the Faculty of Social and Political Sciences, Universitas Tidar, selected through incidental sampling. Data were collected using an online questionnaire with a Likert scale and analyzed using descriptive statistics and reliability testing with Cronbach’s Alpha. The results indicate that students’ interest in organizational participation is generally positive, as reflected in their agreement on various indicators such as enjoyment, organizational involvement, and perceived benefits in skill development. Internal factors such as motivation and self-confidence, as well as external factors such as organizational environment, communication, and program quality, influence participation levels. However, a considerable proportion of neutral responses suggests that organizational commitment is not yet fully optimal. Therefore, student organizations play a strategic role in developing soft skills, leadership, and career readiness, while requiring continuous improvement to enhance student participation. Student participation is influenced by internal and external factors. Internal factors include self-motivation, self-confidence, and the desire to gain new experiences. Meanwhile, external factors include the organizational environment, communication between members, peer support, and the quality of the organization's work programs. However, there were still neutral responses, indicating that student commitment to organizational participation is not yet optimal. Therefore, student organizations play a crucial role in developing students' soft skills, leadership skills, organizational experience, and future career readiness.